Spatial behavior of soil chemical attributes in an area of Black Indian Soil with pasture cultivation - Lima, Alan Ferreira Leite de; Campos, Milton César Costa; Silva, Laércio Santos [UNESP]; Brito Filho, Elilson Gomes de; Cunha, José Maurício da; Mantovanelli, Bruno Campos; Oliveira, Flávio Pereira de (Revista Brasileira de Geografia Fisica, 2021)
Spatial mapping of soil chemical attributes is essential for sampling efficiency and agricultural planning management, ensuring a regional development and sustainability of the unique characteristics of archaeological black earths (ABEs). Thus, this study was developed aiming at assessing the spatial variability and sampling density of chemical attributes in soils of ABEs under pasture. A sampling grid of 56 × 80 m with regular spacings of 8 m was installed in the experimental area and samples were taken from the crossing points at depths of 0.0–0.05, 0.05–0.10, and 0.10–0.20 m, totaling 264 georeferenced points. The chemical attributes pH, OC, Ca, Mg, K, P, Al, and potential acidity were determined in these samples, while CEC, SB, V, t, T, and m were calculated. The attributes present a spatial dependence varying from strong to moderate, being Al3+ the only chemical attribute that does not present a spatial dependence structure in the assessed depths. Scaled semivariograms satisfactorily reproduce the spatial behavior of attributes in the same pattern of individual semivariograms. Sampling density is higher at a depth of 0.0–0.05 m. The decrease in the variability in the attributes in depth proves that the pasture management affects the soil more superficially.
Keywords: Amazonian soils; geoestatistic; management